Management of Peripheral Pulmonary Emboli with the Use of Transvenous Catheter‐Directed Thrombolysis and Right Ventricular Assist Device. Issue 5 (10th September 2013) - Said, Sameh M.; Salhab, Khaled F.; Joyce, Lyle D.
Abstract Objectives: Pulmonary emboli (PE) can result in significant hemodynamic instability that requires urgent intervention; however, the management of peripheral emboli has been controversial. Patients and Methods: We present two patients in whom a right ventricular assist device (RVAD) was used in treating peripheral pulmonary embolism, applying the technique of pulmonary artery catheter‐directed thrombolysis after resuscitation with an RVAD. Results: The clot burden was not suitable for surgical embolectomy due to its peripheral locations. The patients' hemodynamic conditions improved with thrombolytic therapy and gradually were weaned off the RVAD. Follow‐up scans showed near resolution of all PE. Conclusion: Catheter‐directed thrombolysis with an RVAD as an adjunct should be considered in management of peripheral PE. doi: 10.1111/jocs.12185 (J Card Surg 2013;28:611–615)